Analysis of Affixation on “Bertaut” Song Lyrics by Nadin Amizah: a Morphological Study - Ade Kusmana (Journal on Education, 2021)
This research was conducted using qualitative methods. The data used is taken from the lyrics of Nadin Amizah's song on the song entitled "Bertaut" which is available on the internet site. The theory used is affixation, affixes, and forms of affixes. The problem discussed is the use of affixes in the song lyrics in the song. From the results of the study, it was shown that there were many uses of affixation in Nadin's song lyrics. There are 115 words that contain affixes in the lyrics of the linked song. Of the 115 data found for affixed words, prefixes had the highest percentage of use, namely 19 data consisting of the prefixes ber, me-, se-, di- and ter-. The prefix that is most found is the prefix meN-, while the prefix that occurs the least frequently is the prefix te(R)-. The suffixes found in 31 data consist of –nya, -kan, -an, and –i suffixes. The suffix that is most found is the suffix -an, while the suffix that occurs the least frequently is the suffix -nya, -kan, -i. and no Confix found.